(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
In Winner Take Nothing Hemingway deals with his notion of man. In these stories he records the protagonist’s state of mind and behaviour in a situation of crisis in life. From these stories two sets of reactions and states of mind emerge – one in which a man is driven to the point of soul-weariness where desperate acceptance becomes synonymous with courage, and the other in which the protagonist struggles against heavy odds in the face of defeat and though he may be apparently defeated, he emerges as the undefeated and his victory lies in the nobility of his struggle. In these stories it is the individual who has to face the trials alone, that is, he has to rely completely on himself, and this “incurable reliance on the individual” as Leo Gurko observes, “makes Hemingway the great contemporary inheritor of the romantic tradition”.